2011
DOI: 10.1096/fj.10-179267
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol regulation of receptor‐interacting protein 140 via microRNA‐33 in inflammatory cytokine production

Abstract: Receptor interacting protein 140 (RIP140) is a nuclear receptor coregulator that affects a wide spectrum of biological processes. It is unclear whether and how the expression level of RIP140 can be modulated and whether RIP140 is involved in inflammatory diseases. Here, we examine how intracellular cholesterol regulates RIP140 expression, and we evaluate the effect of RIP140 expression on macrophage proinflammatory potential. Macrophages treated with modified low-density lipoprotein express higher RIP140 mRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
71
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 50 publications
1
71
1
Order By: Relevance
“…For example, miR-33 was recently reported to repress the tumor suppressor p53 (50); we and others have reported that p53-deficient mice display enhanced proinflammatory gene expression in response to LPS due to derepression of NF-B (51,52). Alternatively, the potential for miR-33 to suppress inflammation in some contexts is also suggested by a recent report that miR-33 represses the NF-B co-activator receptor-interacting protein-140 (53).…”
Section: Mir-33 Regulates the Innate Immune Responsementioning
confidence: 86%
“…For example, miR-33 was recently reported to repress the tumor suppressor p53 (50); we and others have reported that p53-deficient mice display enhanced proinflammatory gene expression in response to LPS due to derepression of NF-B (51,52). Alternatively, the potential for miR-33 to suppress inflammation in some contexts is also suggested by a recent report that miR-33 represses the NF-B co-activator receptor-interacting protein-140 (53).…”
Section: Mir-33 Regulates the Innate Immune Responsementioning
confidence: 86%
“…Similarly, when Srebp-1c is induced during hyperinsulinemia or insulin resistance, miR-33b is cotranscribed and works to reduce cellular fatty acid oxidation by targeting carnitine O-octanoyltransferase (CROT), carnitine palmitoyltransferase 1A (CPT1a), hydroxyacyl coenzyme A (hydroxyacyl-CoA) dehydrogenase subunit beta (HADHB), and AMP kinase subunit alpha (AMPK␣), as well as insulin signaling, by targeting insulin receptor substrate 2 (IRS2) and sirtuin 6 (SIRT6) (23,24). In addition, we and others have recently shown that miR-33 contributes to the regulation of cholesterol and fatty acid homeostasis by targeting key transcriptional regulators of lipid metabolism, including steroid receptor coactivator 1 (SRC1), steroid receptor coactivator 3 (SRC3), nuclear transcription factor Y, gamma (NFYC), and nuclear receptor-interacting protein 1 (RIP140) (25).…”
mentioning
confidence: 99%
“…Supporting this finding, we previously found that the level of RIP140 is dramatically elevated in macrophages of HDF-induced obese mice. 14,19 Thus, HFD-associated obesity could involve elevating RIP140 expression, which would induce not only M1 monocyte recruitment but also M1 ATM polarization (or repress M2 ATM polarization). Conversely, reducing RIP140 levels in monocytes would reduce M1 monocyte recruitment and M1 ATM polarization (or derepress M2 ATM polarization).…”
mentioning
confidence: 99%